2016
DOI: 10.1111/opo.12293
|View full text |Cite
|
Sign up to set email alerts
|

Using magnetic resonance imaging to assess visual deficits: a review

Abstract: PurposeOver the last two decades, magnetic resonance imaging (MRI) has been widely used in neuroscience research to assess both structure and function in the brain in health and disease. With regard to vision research, prior to the advent of MRI, researchers relied on animal physiology and human post‐mortem work to assess the impact of eye disease on visual cortex and connecting structures. Using MRI, researchers can non‐invasively examine the effects of eye disease on the whole visual pathway, including the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 186 publications
(307 reference statements)
1
66
0
5
Order By: Relevance
“…A number of studies have recently reported changes in white matter microstructure along the primary visual pathways as a result of ophthalmic eye disease [see (Prins et al 2016b;Brown et al 2016;Wandell 2016;Rokem et al 2017) for reviews]. Major examples of impaired white matter tissue microstructure within the primary visual pathways have shown that retinitis pigmentosa (Pan et al 2007), Leber hereditary optic neuropathy (Barcella et al 2010;Milesi et al 2012;Rizzo et al 2012;Ogawa et al 2014), amblyopia (Allen et al 2015;Duan et al 2015), glaucoma (Dai et al 2013;Engelhorn et al 2012;Garaci et al 2009;Lee et al 2014;Hernowo et al 2011) and optic neuritis (Ciccarelli et al 2005;Sergott 2011;Li et al 2009) can affect white matter microstructure estimated in vivo using either diffusion-weighted magnetic resonance imaging methods or volumetric analyses.…”
Section: The Visual White Matter For Predicting Behavioral Function mentioning
confidence: 99%
“…A number of studies have recently reported changes in white matter microstructure along the primary visual pathways as a result of ophthalmic eye disease [see (Prins et al 2016b;Brown et al 2016;Wandell 2016;Rokem et al 2017) for reviews]. Major examples of impaired white matter tissue microstructure within the primary visual pathways have shown that retinitis pigmentosa (Pan et al 2007), Leber hereditary optic neuropathy (Barcella et al 2010;Milesi et al 2012;Rizzo et al 2012;Ogawa et al 2014), amblyopia (Allen et al 2015;Duan et al 2015), glaucoma (Dai et al 2013;Engelhorn et al 2012;Garaci et al 2009;Lee et al 2014;Hernowo et al 2011) and optic neuritis (Ciccarelli et al 2005;Sergott 2011;Li et al 2009) can affect white matter microstructure estimated in vivo using either diffusion-weighted magnetic resonance imaging methods or volumetric analyses.…”
Section: The Visual White Matter For Predicting Behavioral Function mentioning
confidence: 99%
“…Similar to the cases of logotherapy in patients with speech disorders or early kinesitherapy in patients with motor dysfunction, visual impairments require complex management [9][10][11][12]. It is essential that patients with visual disorders are thoroughly examined by a neurologist and ophthalmologist and undergo follow-up neuroimaging visualising and assessing the extent of cerebral stroke (preferably using MRI) as well as perimetry tests [13][14][15]. Complex medical attention, objectivisation of disorders, and evaluation of prognosis favourably affect the patient`s mental condition, which prevents reactive mood disorders enhancing disability [16].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are few methods for non-invasively measuring tissue deformation over the whole globe, which include ultrasound, optical coherence tomography (OCT), and computed tomography (CT), but they all have important limitations (Bajwa et al, 2015; Brown et al, 2016; Fortune, 2015). Ultrasound has excellent penetration depth allowing for quantitative biomechanical analysis of the sclera and cornea, but insufficient resolution to discern the fine structures of the optic nerve head (ONH) (He and Liu, 2009; Palko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%